ADAPTASI PERMUDAAN POHON Gyrinops versteegii (Gilg.) Domke (AKUSUK) SEBAGAI PENGHASIL GAHARU, TERHADAP LINGKUNGAN CAHAYA DI TEGAKAN ALAM GUNUNG TIMAU, NUSA TENGGARA TIMUR - , Sujarwo Sujatmoko ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Light is assumed as one critical factor responsible for growth stagnation of agarwood tree (G. versteegii) both in conservation and cultivation activities. Scientific information on adaptation response to light is needed to formulate proper silvicultural treatment for light environment manipulation. This study is aimed to analyze adaptation response to light environments and their effect on height of G. versteegii. Sample trees of seedling, sapling and poles of G. versteegii were chosen following vegetation survey on G. versteegii natural population located in Mount Timau, East Nusa Tenggara. Tree height, branchless stem, diameter, and relative light intensity (ICR) were measured on each sample tree. Leaf area (LD), water content (KA), Leaf Dry Matter Content (LDMC), Specific Leaf Area (SLA), Specific Leaf Weight (SLW), dan Chlorophyll index (CI) were measured from leaf samples of each tree chosen. Data were analyzed with descriptive statistics, ANOVA, plasticity index, correlation and multiple linear regression. Seedlings, saplings, and poles of G. versteegii were found in 5.34-29.92%, 10.04-43.25%, 33.53-46.32% range of ICR respectively. Those three growth levels were significantly different on LD, KA, LDMC, SLA, SLW, and CI showing that each level adapted to different light environments. Plasticity index decreased with increasing growth level reflecting the decreasing of leaf adaptation response with growth. Percent of branchless stem height had significantly strong correlation with relative light intensity (r=0.623, sig. 0.000). Multiple linear regression analysis show that LD, SLA, CI and ICR were significantly correlated and affect tree height of G. versteegii with regression coefficient of 0.857